2012
DOI: 10.1371/journal.pone.0044164
|View full text |Cite
|
Sign up to set email alerts
|

A New Avenue for Classification and Prediction of Olive Cultivars Using Supervised and Unsupervised Algorithms

Abstract: Various methods have been used to identify cultivares of olive trees; herein we used different bioinformatics algorithms to propose new tools to classify 10 cultivares of olive based on RAPD and ISSR genetic markers datasets generated from PCR reactions. Five RAPD markers (OPA0a21, OPD16a, OP01a1, OPD16a1 and OPA0a8) and five ISSR markers (UBC841a4, UBC868a7, UBC841a14, U12BC807a and UBC810a13) selected as the most important markers by all attribute weighting models. K-Medoids unsupervised clustering run on SV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Each attribute 346 weighting system uses a specific pattern to define the most important SSR fragment 347 alleles. Thus, the results may be different (Baumgartner et al, 2010), as has been 348 highlighted in previous studies (Ashrafi et al, 2011;Beiki et al, 2012;Ebrahimi et al 349 2011). The results showed that attribute subset selection can be beneficiary both to 350 processing time and getting more accurate results.…”
Section: Data Cleaning Deals With Detecting and Removing Errors And Imentioning
confidence: 78%
See 2 more Smart Citations
“…Each attribute 346 weighting system uses a specific pattern to define the most important SSR fragment 347 alleles. Thus, the results may be different (Baumgartner et al, 2010), as has been 348 highlighted in previous studies (Ashrafi et al, 2011;Beiki et al, 2012;Ebrahimi et al 349 2011). The results showed that attribute subset selection can be beneficiary both to 350 processing time and getting more accurate results.…”
Section: Data Cleaning Deals With Detecting and Removing Errors And Imentioning
confidence: 78%
“…data and were used to remove redundancy and co-linearity, useless or duplicated 343 attributes in order to improve the quality of data which results in a smaller database 344 (Ashrafi et al, 2011;Beiki et al, 2012). More than 7% of the attribute alleles 345 discarded when these algorithms were applied on the original dataset.…”
Section: Data Cleaning Deals With Detecting and Removing Errors And Imentioning
confidence: 99%
See 1 more Smart Citation
“…These mentioned approaches have been taken to specify important structural attributes, prediction and classification of protein thermo-stability (Ebrahimi et al 2009), P glycoprotein pump (Hammann et al 2009) halo-stability , olive cultivars (Beiki et al 2012), α-linolenic acid content (Zinati et al 2014) as well as genotype discrimination (Nasiri et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This classifier has been widely used before (for more details see (West 2003 Baseri et al 2011). Two models of Naïve Bayse (returns classification model using estimated normal distributions) and Naïve bayse kernel (returns classification model using estimated kernel densities) (Beiki et al 2012) used and the model accuracy in predicting the type of lung tumor calculted.…”
Section: Methodsmentioning
confidence: 99%